2020
DOI: 10.1039/d0tc02399j
|View full text |Cite
|
Sign up to set email alerts
|

A fast response, self-powered and room temperature near infrared-terahertz photodetector based on a MAPbI3/PEDOT:PSS composite

Abstract: Organic–inorganic halide perovskite with low thermal conductivity, high Seebeck coefficient and high carrier mobility are promising thermoelectric materials for near infrared (NIR) and terahertz (THz) photodetector (PD). Here, we report...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 41 publications
0
32
0
3
Order By: Relevance
“…Figure S9, Supporting Information, shows that DSCT‐produced Sn–Pb perovskite NIR PDs can achieve a NEP as low as 4.79 × 10 −14 W Hz −1/2 at 940 nm, which is lower than inorganic‐, perovskite/quantum dots‐ and organic semiconductor‐based NIR PDs. [ 55–57 ]…”
Section: Resultsmentioning
confidence: 99%
“…Figure S9, Supporting Information, shows that DSCT‐produced Sn–Pb perovskite NIR PDs can achieve a NEP as low as 4.79 × 10 −14 W Hz −1/2 at 940 nm, which is lower than inorganic‐, perovskite/quantum dots‐ and organic semiconductor‐based NIR PDs. [ 55–57 ]…”
Section: Resultsmentioning
confidence: 99%
“…The TE materials have been further developed for use in correlated PTE detectors in terms of the PTE effect at the interface between different materials, such as graphene‐metamaterials, graphene single‐bilayer interface junctions, CNTs electrodes, and phosphorus device with asymmetric metallization 11,12,94,94,95 . Zhang et al 96 demonstrated a sensitive NIR and THz photodetector based on the photoelectric phenomenon that appeared in CH 3 NH 3 PBI 3 (MAPbI 3 ) and PEDOT:PSS hybrid composite with wide absorption range, large light absorption coefficient, and good electrical properties. The device exhibited a stable and repeatable response to 1064 nm and 2.54 THz irradiation at room temperature.…”
Section: Flexible Devices and Smart Elements Based On Ote Materialsmentioning
confidence: 99%
“…度。2016 年,Deng 等人 [36] 研究了金属-石墨烯条带-金属结构太赫兹光热电响应。当太赫兹光从 器件一端移至另一端时,器件中的光响应呈现反对称分布(图 4a)。当太赫兹照在石墨烯-金属 交界处时,器件两端的温差最大,从而得到最大的光响应(8.4 mV/W);当太赫兹照在器件中 间时,器件两端温差为零,此时光响应为零。这表明光响应的来源是不对称的热分布,与光热 电原理相符合。然而,单层石墨烯对太赫兹波的吸收较低,与衬底的热交换较大,这制约了探 测器的性能。2019 年,清华大学 Wen 等人 [37] 使用氧化还原法制备了自支撑的石墨烯薄膜,进一 步优化了石墨烯探测器的性能。较厚的石墨烯薄膜和悬空结构提升了材料对太赫兹的吸收并降 低了热损失,进而提高了光热电响应。2020 年,Chen 等人 [38] 使用人工微结构对石墨烯探测器进 压 [36] ;(b)不同尺寸人工微结构对石墨烯太赫兹吸收的增强效果,图中 d 的单位为 μm [38] ; (c)三维石墨烯吸收体增强碳纳米管的光热电响应 [39] (文献授权自 2019 美国化学会); (d)NbS3 器件的热扩散长度 [23] ;(e)离子液体调控对单壁碳纳米管探测器的性能影响 [21] (文 献授权自 2018 美国化学会);(f)MAPbI3,PEDOT:PSS 和 MAPbI3/PEDOT:PSS 的太赫兹吸 收谱 [40] Fig. 4 Different types of asymmetric illumination terahertz PTE detectors and optimization methods.…”
Section: 太赫兹光热电探测方法研究进展unclassified
“…Copyright 2019 American Chemical Society); (d) The thermal decay length of the NbS3 detector [23] ; (e) The influence of ionic liquid control on the performance of the single-walled carbon nanotube detector (Reprinted with permission from [21] . Copyright 2018 American Chemical Society); (f) THz absorption spectra of MAPbI3, PEDOT:PSS and MAPbI3/PEDOT:PSS [40] 2020 年, Chen 等人 [39] 用类似的方法研究了三维石墨烯的太赫兹光热电响应。相较于单层 石墨烯,三维石墨烯具有更高的光吸收率,提升了光热转化效率,从而非常适合作为太赫兹吸 收体。在三维石墨烯吸收体的增强下,单壁碳纳米管光热电探测器性能提高了一个量级(图 4c)。 应和等离子体波辅助效应 [42,43] 。等离子体波辅助效应是利用材料中的电子受入射电磁场的驱动 产生集体态行为进行太赫兹探测 [44~46] 。在栅压调控下,器件能够呈现以等离子波辅助效应为主 和以光热电效应为主两种不同的工作状态 [47] 。 2012 年,Vicarelli 等人 [48] 提出基于非对称电极结构的器件,在 300 GHz 下具有光热电响应。 2015 年, Viti 等人 [19] 详细分析了黑磷光热电太赫兹探测器中的光热电信号。在栅压调控下,器 件的光响应随黑磷塞贝克系数变化而变化,这证明光电压主要来源于光热电效应。2016 年,他 们 [20] 进一步研究了温度对黑磷太赫兹光热电探测器的影响。随着温度的降低,黑磷中载流子迁 移率提高且热噪声降低,这大幅提高了黑磷探测器性能。 黑磷在空气中很不稳定,会与水和氧气发生反应,影响探测器的稳定性。为了解决这一问 题,一方面可以对黑磷表面进行封装,例如使用氮化硼-黑磷-氮化硼范德瓦尔斯异质结来对黑 磷进行保护 [20] ;另一方面也可以对黑磷进行掺杂。掺有 Te 或 Se 的黑磷具有更好的载流子运输 性能和更好的环境稳定性,并且带隙明显降低(从 2.15 eV 降至 1.9 eV) [49] 。2019 年,Viti 等人 ;(c)探测器性能随硒掺杂黑磷厚度的变化 [50] ;(d)氮化硼-石墨烯-氮化硼器件中形成的 p-n 结 [47] ;(e)氮化硼-石墨烯-氮化硼器件中光热电响应随栅压的变化 [47] ;(f)氮化硼-石墨 烯-氮化硼超快太赫兹探测器 [22] 。(文献授权自 2020 美国化学会) of the device with asymmetric electrodes [19,51] ; (c) The detector performance changes as a function of the flake thickness [50] ; (d) The p-n junction formed in BN-graphene-BN device [47] ; (e) The PTE response changes with the gate voltage in BN-graphene-BN device [47] ; (f) An ultrafast BN-graphene-BN terahertz detector (Reprinted with permission from [22] . Copyright 2020 American Chemical Society).…”
Section: 行优化。人工微结构能在石墨烯中产生局域的电磁共振,从而提高其对太赫兹波的吸收,提升unclassified
See 1 more Smart Citation